Find the value of x that satisfies lo g 3 ( lo g 9 x ) = lo g 9 ( lo g 3 x ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice solution. Thank you.
lo g 3 ( lo g 9 x ) = lo g 9 ( lo g 3 x ) =
9 lo g 3 ( lo g 9 x ) = 9 lo g 9 ( lo g 3 x )
3 2 lo g 3 ( lo g 9 x ) = lo g 3 x
3 lo g 3 ( lo g 9 x ) 2 = lo g 3 x
( lo g 9 x ) 2 = lo g 3 x
( lo g 3 9 lo g 3 x ) 2 = lo g 3 x
2 2 ( lo g 3 x ) 2 = lo g 3 x
4 1 = lo g 3 x 1
x = 8 1
Nice solution. Thank you.
But if x=1 u will get
-∞=-∞
-∞ is not a number, so you can't say -∞=-∞ is true because you can't equate two non-numbers together.
Problem Loading...
Note Loading...
Set Loading...
Let x = 9 n . Then
lo g 3 ( lo g 9 x ) = lo g 9 ( lo g 3 x )
lo g 3 ( lo g 9 9 n ) = lo g 9 ( lo g 3 9 n )
lo g 3 ( lo g 9 9 n ) = lo g 9 ( lo g 3 3 2 n )
lo g 3 n = lo g 9 2 n
9 lo g 3 n = 2 n
3 2 lo g 3 n = 2 n
3 lo g 3 n 2 = 2 n
n 2 = 2 n
Since n ≤ 0 gives an extraneous solution for x , n = 2 , which means x = 9 2 = 8 1 .